Relationship Between Parents Parents And Social Behavior Of Mental Children In SDLB State PK-PLK Bulukumba Regency - Nadia Alfira; Muriyati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2017)
In the world, the number of sufferers of mental retardation is getting higher. Based on data from the World Health Organization (WHO) in 2011 the number of people with mental retardation in the world reached 0.5-2,%, the incidence ranged from 3-4 cases per 1000 children, Indonesia ranks first in the world. The purpose of this study was to determine the relationship between parenting style and social behavior of children with mental retardation in SDLB Negeri PK-PLK Bulukumba Regency in 2016. This study used a quantitative analytic design with a cross-sectional approach. Samples taken in total sampling amounted to 27 respondents. Primary data collection by questionnaire and observation sheet. Fisher's test results with significance level (p <0.05) obtained p = 0.027 <0.05. Then it can be concluded that there is a significant relationship between parenting parents with the social behavior of mental retardation children in SDLB Negeri PK-PLK Bulukumba Regency in 2016 Suggestions That this study can add to the treasury of science and can be used as reading material for children's nursing in the development of science So that this research can be information material for parents to be able to better educate children in mentally retarded children.